Neural therapy in the treatment of congenital megaesophagus in dog: case report - Lima Gonçalves, Bruna; Gonçalves, Bruna Aparecida Lima; Vianna, Leonardo Rocha; Andrade, Camila de Castro (Pubvet, 2019)
Neural Therapy (NT) began in 1905 with the discovey of the first syntetic anesthetic, the procain. The Neural Therapy Scientific base began with the russians Pavlov and Speransky, later, with the German brothers Heneke, and also Pischinger and Hans H. Reckeweg have importance, among others. It is practiced in Austria, Germany, Argentina, Brazil, Canada, Chile, Colombia, Costa Rica, Cuba, Spain, United States, Mexico, Switzerland, Turkey and some another country. It consists in a regulatory therapy that seeks to activate the body self-regulating mechanism through the apliccation of local anesthetics in low concentrations in certain body regions, like acupuncture points, scars, articulations, intravenous, ganglia, among others. This study aims to demonstrate the effectiveness of Neural Therapy in an animal with congenital mesaesophagus.